Impact of PTSD on post-concussive symptoms, neuropsychological functioning, and pain in post-9/11 veterans with mild traumatic brain injury. (October 2018) - Aase, Darrin M.; Babione, Joseph M.; Proescher, Eric; Greenstein, Justin E.; DiGangi, Julia A.; Schroth, Christopher; Kennedy, Amy E.; Feeley, Stacey; Tan, Michelle; Cosio, David; Phan, K. Luan
Highlights: PCS, neuropsychological functioning, and pain-related variables were measured in 90 veterans. Veterans with mTBI and PTSD were compared to those without PTSD and a comparison group. Veterans with mTBI and PTSD reported more PCS and performed worse on measures of recall. Those with mTBI and PTSD had poorer pain coping relative to both other groups. Abstract: Prior work suggested that post-traumatic stress disorder (PTSD) worsens post-concussive symptoms (PCS), neuropsychological functioning, and pain-related outcomes in post-9/11 veterans. However, the impact of PTSD in the context of mild traumatic brain injury (mTBI) is not entirely clear. We evaluated possible differences among veterans with deployment-related mTBI with and without PTSD, and a comparison group. We hypothesized that veterans with comorbid mTBI and PTSD would report more PCS, perform worse on neuropsychological tasks, and report greater pain intensity and maladaptive pain coping relative to those without PTSD. Ninety (15 female, 75 male) post-9/11 veterans completed measures of psychiatric functioning, PCS, deployment-related mTBI, pain intensity, pain coping, and a brief neuropsychological evaluation. Veterans with comorbid mTBI and PTSD reported significantly higher PCS across domains, and greater pain intensity and maladaptive coping. They also performed more poorly on measures of recall, but not on measures of attention, encoding, or executive functioning. Findings suggest that PTSD results in greater PCS in the context of mTBI, and is associated with greater pain catastrophizing, worse recall, greater pain intensity, and greater illness-focused coping than in mTBI alone. PCS symptoms, recall, and pain coping may be of clinical importance for post-9/11 veterans with the "polytrauma triad."